2008
DOI: 10.1002/prot.22097
|View full text |Cite
|
Sign up to set email alerts
|

Ligand preference and orientation in b‐ and c‐type heme‐binding proteins

Abstract: Hemes are often incorporated into designed proteins. The importance of the heme ligand type and its orientation is still a matter of debate. Here, heme ligands and ligand orientation were investigated using a nonredundant (87 structures) and a redundant (1503 structures) set of structures to compare and contrast design features of natural b- and c-type heme-binding proteins. Histidine is the most common ligand. Marked differences in ligation motifs between b- and c-type hemes are higher occurrence of His-Met i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 79 publications
4
59
0
Order By: Relevance
“…To our knowledge, only one example of Gln-Fe coordination (for an engineered cytochrome c peroxidase [40,41]) and one example of His/Asn coordination (for a c cytochrome from Rhodobacter sphaeroides [42]) have been documented. The rarity of CONH2 coordination is confirmed in a recent survey of heme proteins [43]. Tyr22 (B10) was therefore considered for direct interaction with the ferric iron in S6803 rHb-R.…”
Section: Variant Rhb-rs In the Absence Of Added Ligandmentioning
confidence: 74%
“…To our knowledge, only one example of Gln-Fe coordination (for an engineered cytochrome c peroxidase [40,41]) and one example of His/Asn coordination (for a c cytochrome from Rhodobacter sphaeroides [42]) have been documented. The rarity of CONH2 coordination is confirmed in a recent survey of heme proteins [43]. Tyr22 (B10) was therefore considered for direct interaction with the ferric iron in S6803 rHb-R.…”
Section: Variant Rhb-rs In the Absence Of Added Ligandmentioning
confidence: 74%
“…The training set consists of 75 heme protein chains, derived from the nonredundant dataset of 89 heme proteins prepared by Fufezan et al [9]. After removing 14 chains whose HET group codes are not labeled as "HEM", we obtained the remaining 75 heme protein chains as the training set (PHeme-75).…”
Section: A Datasetsmentioning
confidence: 99%
“…For training and testing, we used the datasets of heme proteins in previous studies [3,9]. The training set consists of 75 heme protein chains, derived from the nonredundant dataset of 89 heme proteins prepared by Fufezan et al [9].…”
Section: A Datasetsmentioning
confidence: 99%
“…Cys, His, Tyr, Lys, and Met) are utilized within the binding pockets of distinct classes of heme-binding proteins to coordinate the iron atom of heme, 7 all known heme oxygenases, including the non-canonical heme-degrading enzymes from S. aureus (IsdG/I) 8 and M. tuberculosis (MhuD), 9 use a strictly conserved His residue as the proximal heme ligand. 6, 10 Coordination of iron by the imidazole side-chain of histidine has been regarded as an essential interaction for HO catalysis, based on the observation that His-to-Ala mutants fail to convert heme to biliverdin in vitro despite still binding heme 1114 and, in the case of HmuO from C. diphtheriae, catalyzing formation of the verdoheme intermediate.…”
mentioning
confidence: 99%
“…13, 15, 16 Furthermore, Cys and Tyr mutants of the proximal heme ligand have also been reported to lack HO activity in vitro , 14 despite the ability of these residues to serve as heme ligands in other types of hemoproteins. 7 These observations have suggested that the His-heme interaction is unique in its ability to support HO activity and is thus required for the conversion of heme to biliverdin within the HO active site.…”
mentioning
confidence: 99%